(untitled) (Medical Forum Monthly, 2020)
Objective: To assess the serum Ferritin levels and chelation therapy in transfusion dependent Thalassemia major children and adolescents in Divisional Headquarters Teaching Hospital, Mirpur, AJK. Study Design: Descriptive Observational Study Place and Duration of Study: This study was conducted at the Thalassemia Center of Divisional Headquarters Teaching Hospital, Mirpur, AJK from Oct, 2019 to March, 2020. Materials and Methods: After taking permission from hospital ethics committee, children with transfusion dependent Thalassemia aged up to 18 years were added in the study after informed written consent. Blood samples were sent for Serum Ferritin levels. Serum Ferritin measurement was done by indirect ELISA kit. Chelation therapy was assessed in terms of Deferasirox Tablets and Desferrioxamine injection. Data were analyzed on SPSS 20 and the correlation between age, gender, serum Ferritin level and chelation therapy were checked. Results: A total of 100 children registered with Thalassemia center, Divisional Headquarters teaching hospital, Mirpur were included in this study. There were 55 (55%) males and 45 (45%) females. There were 18 (18%) children between 1-3 years, 20 (20%) in 4-5 years, 17 (17%) in age group 6-8 years, 30(30%) in 9-15 years and 15 (15%) above 15 years of age. Serum Ferritin monitoring revealed 29 (29%) children having Serum Ferritin level between 500-2500ng/dl, 16 (16%) between 2501-3500ng/dl, 19 (19%) between3501-5000ng/dl, 26(26%) between 5001-9000ng/dl and 10 (10%) were having above 9000ng/dl. Maximum children (29%) were found in 500-2500ng/dl serum Ferritin. Majority (66%) was taking chelation as compared to 34% who were not taking any chelation. A strong association was present between Child’s age and serum Ferritin levels with P-value < 0.001. With increasing age, more number of children were taking chelation as compared to younger age (93.33%) at 15 years of age as compared to (45.00%) at 4-5 years of age. Comparing Gender versus chelation revealed that more females i.e. 33 (73.33%) out of 45 were taking chelation as compared to males (60%) taking chelation. It was observed that chelation percentage increased with increasing Ferritin level with P-value < 0.004. Conclusion: The average serum Ferritin levels are significantly raised as compared to the normal permissible levels in these patients. This is further made worse by the fact that around one third of them are not receiving any kind of iron chelation therapy.